Reframing tradition: how NGOs sell market-based conservation to Indigenous communities—lessons from the Leco community in Bolivia - Rajiv Maher; Nanna Schmidt (Humanities & Social Sciences Communications)
Abstract We examine how a market-based conservation non-governmental organization (NGO) persuaded an Indigenous community in Bolivia to adopt new livelihood practices based on neoliberal conservation principles. These practices required the community to abandon their cherished traditional methods in favor of modern farming techniques. We found the community reluctantly accepted the NGO’s proposed market-based conservation-friendly practices. The community had invited NGO collaboration after a hard-fought battle for land rights and autonomy. To understand the communication strategy for swaying the community, we apply framing theory from communicative and social movements literature. Through analysis of archival data, interviews with NGO officials, and fieldwork in Bolivian communities, we highlight the importance of different framing strategies, especially ‘prognostic’ and ‘motivational’ framing, in persuading Indigenous Leco farmers to adopt market-driven conservation practices. Our study contributes to understanding the relational dynamics involved in implementing market-based conservation within Indigenous communities.